Mirror in the sky the life and music of Stevie Nicks - Morrison, Simon Alexander 1964- (University of California Press, 2022)
"Diva, heroine, icon, and-to the most devoted-a goddess. Stevie Nicks sings of spell casters and dream smiths, stars of the silver screen, her grandmother Alice and Alice in Wonderland, Joan of Arc, the power of sibyls and sylphs. This book tells her story, from the bleached Arizona landscape of her childhood to the strobe-lit Night of a Thousand Stevies celebrations, highlighting throughout her strengths as singer, songwriter, and performer"
Inlcudes bibliogrpahical references and index
Keywords: Nicks, Stevie -- 1948-; Geschichte 1948-; Rocksängerin; USA; Nicks, Stevie; Women singers / United States / Biography; Singers / United States / Biography; Rock musicians / United States / Biography; Biografie